Reproductive late effects and testosterone replacement therapy in male childhood cancer survivors: A population-based study (the Fex-Can study) - Haavisto, Anu (WILEY, 2026)
Childhood cancer survivors are at risk of various endocrine late effects affecting their quality of life. The aim of this study was to assess the prevalence and predictors of endocrine and reproductive outcomes in young adult survivors. A secondary aim was to assess possible associations between testosterone replacement therapy (TRT) and other endocrine, cardiovascular and psychosocial late effects. This nationwide study comprised 1212 male childhood cancer survivors aged 19-40 years, identified through the National Quality Registry for Childhood Cancer in Sweden. Median age at diagnosis during 1981-2017 was 7 (range 0-17) and at study 29 (19-40) years. The study combined self-report survey data with cancer treatment data from the national registry. Hormone-induced puberty was self-reported by 3.8% of the survivors and ongoing TRT by 6.0%. In separate logistic regression analyses, these treatments were associated with hematopoietic stem cell transplantation and cranial radiotherapy. Hormone-induced puberty was additionally associated with younger age at diagnosis. Men with TRT had a higher prevalence of other endocrine deficiencies, cholesterol medication, depressive symptoms and fatigue as well as a lower probability of living with a partner, having a biological child or current occupation. In the total male cohort, 28.2% reported having a biological child. Reassuring reproductive outcomes after less intensive therapies and low frequency of TRT were observed in young adult male childhood cancer survivors treated in the most recent treatment era. However, men with TRT suffered from several other endocrine, cardiovascular and psychosocial late effects, indicating a need for long-term monitoring of this high-risk group.Childhood cancer survivors are at risk of various endocrine late effects affecting their quality of life. This population-based study in a recent cohort of childhood cancer survivors assessed prevalence rates of testosterone replacement therapy and fertility outcomes, providing valuable information for current patients. Among young adult men with a history of childhood cancer, 6% reported ongoing testosterone replacement therapy. Testosterone replacement was associated with self-reported treatment with other hormones and cardiovascular medication as well as psychological and sociodemographic factors. The findings indicate a need for long-term follow-up in male childhood cancer survivors with testosterone substitution. image